Effects of blade airfoil chord length and rotor diameter on aerodynamic performance of straight-bladed vertical axis wind turbines by numerical simulation. (15th February 2023) - Tong, Guoqiang; Li, Yan; Tagawa, Kotaro; Feng, Fang
Abstract: Straight-bladed Vertical Axis Wind Turbines (SB-VAWTs) have recently attracted much attention as they are considered to be an option for wind energy utilization, whether in offshore or urban environments. In this study, the effects of airfoil chord length and rotor diameter (circumference) on the aerodynamic characteristics of SB-VAWTs were explored by numerical simulation. The research object is a three-bladed SB-VAWT fitted with a NACA0018 symmetric airfoil. A dimensionless parameter RCC is proposed, that is, the ratio of the airfoil chord length to the circumference of the rotor. There are 43 different combinations of chord length and rotor diameter designed for the present study, making the RCC ranges between 1.4% and 57.3%. When the length of airfoil chord is constant and the diameter of rotor changes, the recommended RCC is supposed to be approximately 8% for the SB-VAWT. Differently, when the diameter of the rotor is constant and the length of airfoil chord changes, the recommended RCC is supposed to range between 9.5% and 13.4%. Based on the results, it is confirmed that the RCC is a significant parameter for the design of the SB-VAWT. This study is expected to provide a practical reference for the parametric structural design of SB-VAWTs. Highlights: Three-bladed SB-VAWT with NACA0018 symmetric airfoil was selected as the research object. A dimensionless parameter RCC was proposed as the ratio of blade airfoil chord length to rotor circumference. Effect of RCCs between 1.4% and 57.3% on rotor aerodynamics was researched by numerical simulation. The optimal RCCs for airfoil chord length and rotor diameter were analyzed and recommended, respectively.